1993
DOI: 10.1364/josaa.10.001624
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in retinal disease and the computational model of the human-rod response

Abstract: Abnormal rod-receptor activity can be quantitatively assessed in humans by fitting a computational model of the rod's response to the leading edge of the a wave of the electroretinogram. One purpose of the present study was to compare two procedures for fitting the model to the electroretinogram. A computationally simpler method gives comparable results to the more labor-intensive method used previously. This finding holds for both normal observers and patients with retinodegenerative disease that affects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Having found a close correspondence between the two sets of extracted results we are confident that they provide a reasonably accurate measure of the underlying parameters. For families of a ‐wave responses, Hood et al (1993) similarly concluded, under dark‐adapted conditions, that measurement at a fixed time (10 ms) provided a simple and accurate method of extracting the parameters of transduction.…”
Section: Discussionmentioning
confidence: 94%
“…Having found a close correspondence between the two sets of extracted results we are confident that they provide a reasonably accurate measure of the underlying parameters. For families of a ‐wave responses, Hood et al (1993) similarly concluded, under dark‐adapted conditions, that measurement at a fixed time (10 ms) provided a simple and accurate method of extracting the parameters of transduction.…”
Section: Discussionmentioning
confidence: 94%